Understanding the toxicological effects of TiO2 nanoparticles extracted from sunscreens on human keratinocytes and skin explants - Darien Yu De Kwek; Magdiel Inggrid Setyawati; Archana Gautam; Sunil S. Adav; Ee Cherk Cheong; Kee Woei Ng (Particle and Fibre Toxicology, 2024)
Abstract Background Inorganic ultraviolet filters such as titanium dioxide nanoparticles are frequently used in sunscreens. Numerous toxicological studies in vitro and in vivo have been conducted using pristine standard reference nanomaterials of these inorganic filters. While convenient, this approach is not realistic because the complex environment of sunscreen formulations could change the physicochemical properties of the nanoparticles and lead to vastly different toxicological outcomes. Therefore, this study focused on characterizing nanoparticles extracted from commercial sunscreen and evaluating the associated toxicological impacts upon exposure to human keratinocytes and human skin explants. Results Titanium dioxide nanoparticles were extracted from commercial sunscreens and thoroughly characterized. The identity of the associated molecular corona on the extracted nanoparticles was also evaluated. Cell metabolic and proliferation profiles, mitochondrial superoxide activity, reactive oxygen species levels, and genotoxicity induced through exposure to the nanoparticles were studied in vitro using a human keratinocyte cell line. The cell response was significantly different after treatment with pristine nanoparticles compared to corresponding sunscreen-extracted nanoparticles. Pristine spherical nanoparticles resulted in more pronounced toxicity in 2D cultured keratinocytes compared to extracted nanoparticles but did not impact wound-edge migration significantly in 3D ex vivo human skin explant models. Additionally, extracted rod-shaped nanoparticles had greater toxic impacts in keratinocytes in vitro and retarded wound-edge migration in the ex vivo model compared to the extracted spherical nanoparticles. Nevertheless, these heightened cell responses were not associated with any increase in phosphorylated γH2AX (which is indicative of DNA damage) both in vitro and ex vivo. Conclusions This study shows the feasibility of extracting nanoparticles from personal care products such as sunscreens to obtain relevant forms to model real-life exposure scenarios. Overall, sunscreen-extracted nanoparticles were found to be less toxic compared to pristine equivalents but retarded wound-edge migration more significantly. Skin explant cultures provide a more realistic alternative to monolayer cell cultures, although the differential outcomes between the models need more in-depth evaluation.